Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/dom.12049
|View full text |Cite
|
Sign up to set email alerts
|

Components of metabolic syndrome and 5‐year change in insulin clearance – the Insulin Resistance Atherosclerosis Study

Abstract: Aims Cross-sectional evidence indicates that abdominal adiposity, hypertension, dyslipidemia and glycemia are associated with reduced metabolic clearance of insulin (MCRI). Little is known about the progression of MCRI and whether components of metabolic syndrome are associated with the change in MCRI. In this study, we examined the association between components of metabolic syndrome and the 5-year change of MCRI. Methods and Materials At baseline and 5-year follow-up, we measured fasting plasma triglycerid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 38 publications
2
16
0
Order By: Relevance
“…This is consistent with prior studies linking decreased insulin clearance with an adverse metabolic profile and increased risk of diabetes [4, 12, 3739]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with prior studies linking decreased insulin clearance with an adverse metabolic profile and increased risk of diabetes [4, 12, 3739]. …”
Section: Discussionsupporting
confidence: 93%
“…Other studies have shown a positive correlation between HDL-C and MCRI; however, the multivariate models in these studies did not include apoA-I [12, 37]. The physical relationship of apoA-I and HDL may explain why HDL-C level did not correlate with MCRI when analyzed jointly.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The inverse association between plasma BCAAs and insulin clearance could be linked through metabolic syndrome. Previous studies have shown that metabolic syndrome is associated with reduced insulin clearance (26,27) and, further, that the gene expression of BCAA catabolic enzymes is reduced in individuals with metabolic syndrome (28). Although the significant association between BCAAs and insulin clearance remained after additional adjustment for waist circumference, HDL cholesterol, systolic blood pressure, and plasma triglycerides, the magnitude of the association was attenuated, suggesting that these components of metabolic syndrome may, in part, link plasma BCAA to insulin clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, only half of the increase in insulin was attributable to increased glycemic load and the other half was due to insulin resistance. Several studies showed that decreased insulin sensitivity was associated with decreased insulin clearance [19,20,21], and reduced insulin clearance correlated with risk of incidence of T2DM [22]. The Insulin Resistance Atherosclerosis Study 5-year follow-up showed a negative correlation between plasma plasminogen activator inhibitor (PAI)-1 concentrations and insulin clearance [23].…”
Section: Discussionmentioning
confidence: 99%